Planning A Successful Future - John E Sestina (Wiley, 2016)
Early in his career as a financial advisor, John Sestina recognized a conflict between charging his clients fees and accepting commissions from product sales. In whose interest was he advising? Five decades later, John is still considered the father of fee-only financial planning. Now, he continues to offer investors the best nonbiased guidance in Planning a Successful Future, a proactive guide to taking care of yourself and your family without leaving it to chance.Before you put money into the market or bonds, or with an advisor, you need to understand what you have, what you want, and your goals along the way. This is your opportunity to work with John and his talented team to develop your own sustainable financial plan based on your realistic goals. Interactive chapters direct you through every step of organizing and strategizing your future wealth, including the most convenient system to organize your data, defining future plans and goals, and insuring the long-term welfare of your family. Everything inside is immediately usable in the real world because it is fully up to date with the most recent changes in the financial planning industry, particularly related to risk management, allocation, tax reduction, and estate planning. It enables you to put your plan into practice with guidance on choosing and working with an advisor, as well as focused investing advice for women, business owners, and physicians. With this book and a calculator, you can determine :